Critical media literacy as curricular praxis - Nam, Siho (Javnost (Ljubljana), 2010)
The current stalemate of mass communication as neither a professional nor a worthwhile academic discipline in U.S. higher education is deeply rooted in the gradual evaporation of the critical in its curriculum. In light of this, this article strives to reclaim "the critical" in media literacy, aiming at three main goals. First, it attempts to problematise the escalating vocationalisation of mass communication education. Second, it seeks to build aphilosophical, theoretical base for critical media literacy, informed by critical educational theories developed by Paulo Freire, Henry Giroux, and others. Third, it aims to identify some core areas of critical media literacy by which to reconfigure mass communication as an interdisciplinary academic field within the larger context of democracy. Ultimately, the article makes the case for repositioning critical media literacy as pedagogy of possibility that opens up a new pedagogical space for alternative, counter-hegemonic mass communication education and practices.
Keywords: United States of America; ZDA; množično komuniciranje; mass media; množični mediji; pismenost; literacy; education; izobraževanje